Structural Equations Modeling Approach: Issues in selecting a University - Simarmata, Justin Eduardo; Mone, Ferdinandus; Chrisinta, Debora (JOIV : International Journal on Informatics Visualization, 2024)
Higher education is a continuation of secondary education that is organized to prepare students to become members of the community with academic or professional abilities. Therefore, selecting a university is essential for helping students acquire knowledge and skills and prepare themselves to be independent individuals. This study intends to determine the distribution of decision-making students who select the university based on factors of academic ability, individual characteristics, psychology, instrumental, and environmental factors. The study's methodology, which involves the collection of primary data from 474 respondents from high schools in the Indonesian-Timor Leste border region, is robust and rigorous, instilling confidence in the reader. The method used for data analysis is quantitative, which involves applying structural equation modeling to identify factors that influence students’ selection of universities. The study results showed that out of the six structural models formed, they could provide evidence that factors such as academic ability, individual characteristics, psychology, instrumental factors, and environment influence students’ selection of universities. This can be seen from the test values of the regression model formed in the structural modeling, which gives a P-value of less than 5%. The variable that provided the largest percentage, partially influencing student interest in selecting a state university, was the school environment, which was 98%. The value was based on the path coefficient of structural equation modeling. These findings have significant implications for the design of university admission processes and the development of student support programs.